Stellaria mcclintockiae (Caryophyllaceae) a new species from Kerala, India - Arya, Sindhu; Kumar, Venugopalan Nair Saradamma Anil; Sojan, Jose; Philip, Alen Alex; Suresh, Veerankutty (Phytotaxa, 2024)
A new species of Stellaria from the Nelliyampathy hills of Palakkad district (Kerala, SW-India) is described and illustrated. The new species can be considered as part of the S. media group but differs from the various species with respect to bracts, sepals, petals, pollen morphology and seed surface architecture. Molecular analyses (ITS) confirmed the validity of the new taxon.